Base system of training and system of direct preparation to competitions in armsport - Bezkorovainyi D.O (Kharkov National Pedagogical University, 2010)
In this article the considered general representations about methods and systems of preparation junior armsportsmen are described; special exercises for employment armsport are resulted; practical recommendations for batching loadings are resulted. The role of armsport is opened as means of physical training, self-management and self-education. The technique of trainings, features of physical preparation and a rule of carrying out of trainings that gives the basis to consider armsport as object of independent scientific - methodical researches is examined. Practical recommendations enable to develop in the future model characteristics of sportsmen, which are engaged armsport.